A Weakening Rheology of Dry Granular Flows With Extensive Brittle Grain Damage in High‐Speed Rotary Shear Experiments. Issue 11 (1st June 2020) - Hu, Wei; Chang, Ching Shung; McSaveney, Mauri; Huang, Runqiu; Xu, Qiang; Zheng, Yangshuai; Yu, Jiefu
Abstract: The puzzle of the unexpectedly high mobility of large geophysical flows has been reported as solved many times since Albert Heim drew attention to it after a disastrous landslide at Elm, Switzerland. Many hypotheses have been proposed to explain the hypermobility; however, no consensus position has emerged in more than a century, and debate rages on. We show a new trend of dense granular flow behavior above average normal stress of 0.3 MPa with weakening at high strain rate, which may be explained by shear‐thinning thixotropy. Experimental results for a given shear rate at normal stresses between 0.3 and 1 MPa show a bifurcation in shear‐resistance behavior. The trend of all our data deviates obviously from the traditional rheological model. We identified three regions of dense granular flow: a static region, an inertial region, and a weakening region at increasing strain rate in grain flows that results in widespread grain breakage. The former two regions agree with the traditional rheological model established at lower normal stresses; however, instead of entering a collisional region, a weakening region appeared. For gravity flows, it is possible for unstable flows to occur for certain combinations of normal stress and shear strain rate. An underlying mechanism of grain crushing and grain crushing‐induced special grain structure may greatly reduce the shear resistance due to thixotropy. The profound weakening provides a natural explanation for the observed high mobility in such geophysical behavior as the long runout of rock avalanches, fault weakening, impact‐crater evolution, and pyroclastic flows. Plain Language Summary: Very dense granular shear flows are intrinsic to many geophysical processes, such as rock avalanches, debris flows, pyroclastic flows, earthquake rupture on gouge‐filled faults, and evolution of impact craters. The rheological behavior of dense granular flows is crucial to the understanding of these high‐stress geophysical processes. Many hypotheses have been proposed to explain the hypermobility; however, no consensus has emerged in more than a century, and debate rages on. We show a new trend of dense granular flow behavior for crushable granular material. This new trend can be explained by the behavior of thixotropy. The granular materials show a profound decrease of shear resistance during prolonged rapid shear, which alters the material structure under the applied shear strain rate and applied normal stress. This provides a natural explanation of hypermobility of dense granular geo‐flows. Key Points: We show a new trend of dense granular flow behavior weakening at high strain rate, which may be explained by shear‐thinning thixotropy We identified three regions of dense granular flow: a static region, an inertial region, and a weakening region A mechanism of grain crushing may greatly reduce the shear resistance due to thixotropy